2019
DOI: 10.2174/1381612825666190321110420
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Beliefs About Medicines and Adherence to Pharmacotherapy in Pregnancy: Opportunities for Community Pharmacists

Abstract: BackgroundDuring pregnancy women might weigh benefits of treatment against potential risks to the unborn child. However, non-adherence to necessary treatment can adversely affect both mother and child. To optimize pregnant women's beliefs and medication adherence, community pharmacists are ideally positioned to play an important role in primary care. ObjectiveThis narrative review aimed to summarize the evidence on 1) pregnant women's beliefs, 2) medication adherence in pregnancy, and 3) community pharmacists'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 71 publications
2
29
0
1
Order By: Relevance
“…This variation in medication use during pregnancy is in line with previous studies showing percentages ranging from 62% for the treatment of chronic psychiatric disorders35 to 93% for the treatment of hypothyroidism 36. Another study showed that patient characteristics such as educational level and occupation influence pregnant women’s perceived risks of medication use 5. We also observed some differences in sociodemographic characteristics between medicated and non-medicated women, such as maternal age, marital status or having previous children.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This variation in medication use during pregnancy is in line with previous studies showing percentages ranging from 62% for the treatment of chronic psychiatric disorders35 to 93% for the treatment of hypothyroidism 36. Another study showed that patient characteristics such as educational level and occupation influence pregnant women’s perceived risks of medication use 5. We also observed some differences in sociodemographic characteristics between medicated and non-medicated women, such as maternal age, marital status or having previous children.…”
Section: Discussionsupporting
confidence: 90%
“…However, adherence to chronic medication during pregnancy is low. Previous studies among pregnant women with various chronic diseases (eg, asthma, epilepsy and inflammatory bowel diseases) have shown that about 40% of these women do not adequately adhere to their medication,4 5 which challenges appropriate management of the underlying maternal disease 6. Suboptimally treated maternal chronic diseases like epilepsy, asthma, diabetes and mental disorders can have a negative impact on the mother and on the unborn child (eg, low birth weight, macrosomia, preterm birth or perinatal mortality) 7–11.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have already shown that women indeed have a higher threshold to use medicines during pregnancy compared with non‐pregnant situations and preferably avoid or delay their use . This medication hesitancy can lead to poor adherence and inadequate use of essential treatment, thereby potentially compromising foeto‐maternal outcomes . Women also tend to overestimate the teratogenic risk of medicines and substances .…”
Section: Introductionmentioning
confidence: 99%